Service quality and customer satisfaction as antecedents of financial sustainability of the water service providers. Issue 8 (4th May 2021) - Murrar, Abdullah; Batra, Madan; Rodger, James
Abstract : Purpose: Service quality and customer satisfaction influence the financial performance of service organizations. Hence, the purpose of this paper is to investigate the path relationship of service quality to customer satisfaction to financial sustainability in the water service sector, which is vital to the sustainable future of mankind. Further, these three interrelated constructs and their dimensions are clearly articulated. Design/methodology/approach: SERVQUAL questionnaire responses were collected from 635 household families, and the financial sustainability indicators of 56 water providers were gathered as well. Cronbach's alpha and factor analysis were conducted to measure the internal consistency and convergent validity. Path analysis was utilized to evaluate the causal diagram by examining the relationships among service quality, customer satisfaction and financial sustainability using the AMOS software package. Findings: The results showed that the five dimensions of service quality explain 58% of the customer satisfaction variation. The responsiveness, empathy, assurance and reliability have significant impact on the customer satisfaction where p < 0.05, while the tangible dimension has an insignificant effect. The results also revealed that customer satisfaction has a significant impact on the financial sustainability indicators of the water providers, where p = 0.000 for the debt collection ratio indicator, and p = 0.003 for the financial efficiency ratio indicator. Research limitations/implications: This research on financial sustainability is based on evidence about service quality and customer satisfaction in the Palestinian water sector. Future research on financial sustainability of the water sector may focus on the pricing mechanism and debt collection of water service. Practical implications: The findings suggest that water providers should recognize the importance of service quality dimensions, which strengthen the customer satisfaction, which, in turn, is a significant driver for their financial sustainability. It is, therefore, sound to draw action-oriented managerial implications from these results. Originality/value: The study adds to the literature of water service sector and is based on empirical evidence from primary data of household families and secondary data of water service providers from developing countries. This paper also contributes toward the strengthening of sustainability of the water service sector in Palestine – a worthy humanitarian cause. The study provides evidence useful for policy makers toward carving out policies aimed at strengthening the financial sustainability of the water service sector.